AN ACHIEVEMENT OF GOOD GOVERNANCE IN LOCAL ADMINISTRATION : A CASESTUDY DONKAEW SUBDISTRICT ADMINISTRATIVE ORGANIZATION AND MUANGKAEW SUBDISTRICT MUNICIPALITY, CHIANG MAI PROVINCE - สถาปนาศุภกุล, วรยุทธ (Community and Social Development Journal, 2018)
The objectives of this paper were 1) to study an achievement of administration according to good governance principle of the administrator in donkaew subdistrict administrative organization and muangkaew subdistrict municipality, mae rim district in chiang mai 2) to compare an achievement of administration according to good governance principle of the administrator in donkaew subdistrict administrative organization and muangkaew subdistrict municipality, mae rim district in chiang mai, and 3) to suggest the way to promoting the administration according to good governance principle of the administrator in donkaew subdistrict administrative organization and muangkaew subdistrict municipality, mae rim district in chiang mai. The study sampling subjects consisted of the people in donkaew subdistrict administrative organization and muangkaew subdistrict municipality, a total of 394. Tools for data collection were questionnaires; statistics for data analysis included frequency, percentage, standard deviation, and t-test and F-test. The Results of the data analysis were presented in descriptive tables. The Results of the research were as follows: 1) the people’s opinions on an achievement of administration according to good governance principle of the administrator in donkaew subdistrict administrative organization and muangkaew subdistrict municipality, in six aspects were rated at a high level. When considering by aspect from high to low rating, it was found that the first was the rule of law, followed respectively by morality, cost-effectiveness, transparence, responsibility, and participation; all were rated at a high level, 2) the hypothesis test showed that the people, who differed in sex and age did not differ in opinion on the achievement of administration according to good governance principle of the administrator donkaew subdistrict administrative organization and muangkaew subdistrict municipality, which was not consistent with the hypothesis; while the people, who differed in level of education and working status, did differ in the aforesaid opinion with statistical significance at 0.05, and 3) with regard to the suggestions on administration according to good governance principle of the administrator in donkaew subdistrict administrative organization and muangkaew subdistrict municipality, it was found that the administrator should have control mechanism for the officers to strictly follow the rules and regulations; the service rendering should be carried out with justice; the administrator had to work wholeheartedly with no favor of the business of their own family or kinsmen and friends. Additionally there should be internal monitor mechanism and more training activity be held; the people should be allowed to inspect the performance of the administrator; and local resources should effectively be utilized.